Removal of Malachite Green from Aqueous Solution by Iraqi Porcelanite Rocks - Muneer. A . AL-Da'amy (Journal of Global Pharma Technology, 2017)
Removal of Malachite greendye has been carried out by using Iraqi Porcelanite rocks as an adsorbent. A series of experiments were undertaken in a batch adsorption technique to access the effect of the process variable i.e. namely initial dye concentration, contact time, adsorbent dose, initial pH, and temperature. Maximum adsorption of malachite green was achieved at the suggested optimum conditions: initial dye concentration (6mg.L-1), weight of adsorbent (0.05 g), pH solution (8.5) and contact time (30 min).Equilibrium data were well represented by the Freundlich model. Thermodynamic parameters were estimated. The negative values of the Gibbs energy indicated the spontaneous nature of the adsorption .The entropy was positive and the positive value of the enthalpy showed that the process is endothermic. The removal of Malachite green dye using Iraqi porcelanite rocks has been studied at different temperatures (298.15, 308.15, 318.15, and 328.15)K to determine the adsorption isotherms .The shapes of the isotherms obtained from the experimental data were found to be comparable in all cases to the (S- curve) type according to Giles classification.Keywords: Adsorption, Porcelanite rocks, Malachite green, Isotherms, Langmuir, Freundlich.